The cultural dimension of global business - Ferraro, Gary P.; Briody, Elizabeth Kathleen (Boston : Pearson, 2013)
Demonstrates how the theory and insights of cultural anthropology can positively influence the conduct of global business. --from publisher description.
Cultural anthropology and global business : Introduction: Global connections ; The perspective of cultural anthropology ; Cultural anthropology and business ; Anthropology's major concept: culture ; Cultural differences in business: challenges and opportunities -- Lenses for understanding culture and cultural differences : Contrasting values ; Context ; Metaphors ; Change -- Communicating across cultures: the nonverbal dimension : The nature of nonverbal communication ; Business introductions ; Interactions among businesspeople -- Communicating across cultures: language : The ideal of linguistic proficiency in global business ; Linguistic diversity ; Language and culture ; Linguistic style ; Language and social context ; Some additional complicating factors ; Information and communication technologies in the 21st century -- Negotiating across cultures : The nature of cross-cultural negotiation ; Where to negotiate ; Effective strategies for international negotiators ; The use of interpreters ; The global negotiator -- Partnering across cultures : Partnership basics ; Meetings as opportunities for collaboration ; Decision-making modes to advance the partnership work ; Partnering relationships and problem solving -- Coping with culture shock : The nature of culture shock ; Minimizing culture shock -- Developing global leaders : Globally oriented firms ; Creating a globally oriented workforce ; The evolving profile of the overseas assignment ; Selection ; Preparation ; In-country support ; Repatriation -- Appendix A. Cross -cultural scenario discussions -- Appendix B. Locating relevant cultural information : The traditional anthropological approach ; Documentary sources useful in developing a cultural profile ; Human resources for culture-specific information ; The search for cultural information upon arrival ; Conclusion.
Includes bibliographical references (pages 268-280) and index.
Keywords: International business enterprises -- Social aspects; Intercultural communication; Technical assistance -- Anthropological aspects